Achieving Consensus on the Values and Activities of all Healthcare Educators: A Mixed-Methods Study - Browne, Julie; Bullock, Alison; Parker, Samuel; Poletti, Chiara; Gallen, Derek; Jenkins, John (Journal of Research in Interprofessional Practice and Education, 2021)
Background: To facilitate a stronger recognition of the importance of the healthcare educator role and clearer communication regarding IPE, consensus is needed regardingn the values and areas of activity that all healthcare educators share, regardless of professional group.Methods and findings: A five-phase consensus process was used, consisting of a survey and search to identify guidance documents, a literature review and text analysis, a face-to-face consensus meeting, a novel workshop to develop organizing principles, and a two-stage Delphi consultation. This consensus process resulted in a nine-item list of shared values and 25 activities sorted into four domains.Conclusion: This article reports the development of a rigorous and collective consensus statement on the core values and activities shared by all healthcare educators. This is a necessary preliminary to establishing the groundwork on which interprofessional educational initiatives can be built.